ChemInform Abstract: A2MnU3O11 (A: K, Rb) and Li3.2Mn1.8U6O22: Three New Alkali‐Metal Manganese Uranium(VI) Oxides Related to Natrotantite. Issue 39 (September 2015) - Read, Cory Michael; Morrison, Gregory; Yeon, Jeongho; Smith, Mark D.; zur Loye, Hans‐Conrad
Abstract Single crystals of the title compounds are prepared from molten chloride fluxes using U3O8, MnCl2, and KCl, RbCl, or LiCl as starting materials (alumina crucible, 900—950 °C, 12 h, 70 and 90% yield for Rb2MnU3O11 and K2MnU3O11, respectively).